2014
DOI: 10.3390/su6031521
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two (or More) Sustainabilities: A Q Methodology Study of University Professors’ Perspectives on Sustainable Universities

Abstract: Abstract:If change for sustainability in higher education is to be effective, change efforts must be sensitive to the institutional culture in which they will be applied. Therefore, gaining insight into how institutional stakeholders engage with the concept of sustainable universities is an important first step in understanding how to frame and communicate change. This study employed Q methodology to explore how a group of professors conceptualize sustainable universities. We developed a Q sample of 46 stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 43 publications
(74 reference statements)
0
29
0
1
Order By: Relevance
“…Prior research has highlighted academic autonomy (i.e., freedom of inquiry of faculties and faculty members) as a significant mediating factor in the uptake of sustainability [40][41][42]. This significance has been explained in two main ways.…”
Section: Institutional Change and Sustainability In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has highlighted academic autonomy (i.e., freedom of inquiry of faculties and faculty members) as a significant mediating factor in the uptake of sustainability [40][41][42]. This significance has been explained in two main ways.…”
Section: Institutional Change and Sustainability In Higher Educationmentioning
confidence: 99%
“…To set the stage for introducing this typology further, it is helpful to appreciate some of the ways in which higher education structures and decision-making processes intersect with ambitions of SHE. The shifting and complex governance structures of higher education have often been cited as a barrier to innovation in SHE, including in relation to both entrenched and emergent aspects of the higher education sector [2,3,31,40].…”
Section: Institutional Change and Sustainability In Higher Educationmentioning
confidence: 99%
“…State of sustainability and state of education include different levels: no change (or "token"); cosmetic reform (education about sustainability); serious greening (education for sustainability) or wholly integrative (sustainable education). A common vision for sustainability in higher education requires institutional change efforts toward sustainability (Sylvestre et al, 2014). However, despite the diffused conviction that universities bear a profound moral obligation to promote ideals of sustainability by incorporating them throughout their institutional dimensions, cultural barriers and resistances to organisational change still exist.…”
Section: Education For Sustainable Development and Education For Sustmentioning
confidence: 99%
“…Exploring lecturers' beliefs about, and understandings of, sustainable development and their views on incorporating it into the curriculum, Cotton et al (2009) revealed a diversity of understandings of 'education for sustainable development' and a range of views on the appropriateness of including sustainable development in the curriculum. In addition, a specific research stream has been developing on Education for Sustainability (EfS) (Corcoran and Wals, 2004;Cotton et al, 2007;Sherren, 2008;Shephard, 2010;Teisl et al, 2010;Sylvestre et al, 2013Sylvestre et al, , 2014Christie et al, 2015) However, the vast literature reveals a highly subjective nature of thinking about the roles of higher education and its teachers with respect to education for sustainability. Shephard and Furnari (2013) attempted to make sense of the complex phenomenon through the viewpoints provided by university teachers.…”
Section: Education For Sustainable Development and Education For Sustmentioning
confidence: 99%
See 1 more Smart Citation